1997
DOI: 10.1111/j.1472-8206.1997.tb00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of okadaic acid on rat uterine contractile responses to different spasmogens

Abstract: In the present study, we examined the effects of okadaic acid, a selective inhibitor of type 1 and 2A protein phosphatases, on the mechanical responses evoked by oxytocin, K(+)- and Na(+)-modified solutions and ouabain in estrogen-primed rat myometrium. Oxytocin elicited a rapid, phasic contraction followed by rhythmic oscillations. The phasic response was partially resistant to the absence of external Ca2+. Okadaic acid (1 microM) and the L-type calcium channel blocker nifedipine (1 microM) abolished the osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Whereas the initial administration of OA had no significant influence on unstimulated uterine contractions, in relation to baseline and controls, this single OA treatment significantly inhibited the responsiveness of mouse uterine horns to OT-stimulated contractions. This OA-induced suppression of OT-stimulated contractions is similar to that recently described in the estrogen-primed rat myometrial strip system [42].…”
Section: Discussionsupporting
confidence: 87%
“…Whereas the initial administration of OA had no significant influence on unstimulated uterine contractions, in relation to baseline and controls, this single OA treatment significantly inhibited the responsiveness of mouse uterine horns to OT-stimulated contractions. This OA-induced suppression of OT-stimulated contractions is similar to that recently described in the estrogen-primed rat myometrial strip system [42].…”
Section: Discussionsupporting
confidence: 87%
“…Hence, PP2A inhibitors are expected to cause smooth muscle contraction. Paradoxically, inhibitor-based studies have shown that Յ1-3 M OA caused relaxation in rat, guinea pig, dog, pig, and bovine vasculature, rat myometrium, and bovine trachea smooth muscles (1,10,11,18,28,29,102,109,211,235). In myometrium, only Ͼ10 M OA produced contraction or temporary contraction and then relaxation, and these contractions were attributed to PP1 inhibition (10,28,29).…”
Section: Role Of Pp2a In Smooth Muscle Contractilitymentioning
confidence: 99%